Absence of Fingerprints- A Case Series - Ferdous, Jannatul; Hoque, Rajiul; Islam, Rafayel; Sharar, Sanya (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Biometric identification with the use of fingerprints being one of the most popular methods in recent times for identity verification all over the world, is extensively used to keep up records and getting through every legislative process in Bangladesh. This newly devised method of identity verification is exposing cases of genetically inherited adermatoglyphia (absence of fingerprints) also termed as, immigration delay disease. The disease is characterized by absence of fingerprints that are seeking legal attention to concerned authorities requiring an alternative standardized method of verification. Only a few isolated cases of the adermatoglyphia, where every offspring has 50% chance of having the disease in an autosomal dominant fashion, have been reported in the whole world till date. Hence an alternative method of verification is required to keep up authentic records for these people and their future generations. This case series study was done on newly identified suspected cases of genetically inherited adermatoglyphia, where six male members from one single-family are suffering from this disease. They are facing problems in everyday life as the absence of fingerprints is restricting them from accessing national ID card, sim card registration, passport, driving license & other services where biometric verification is mandatory to confirm the identity. Ibrahim Card Med J 2022; 12 (1): 64-68